Strategy instruction in listening for lower-intermediate learners of French - Graham, S; Macaro, E (Wiley-Blackwell, 2008)
Scond language listening has historically proved to be a difficult skill. Strategy instruction studies have sought to bring about improvements in subjects' listening but with mixed results. This lack of success might be due to the nature of listening strategy theory and its influence on conceptualizations of listening strategy instruction. The current study, based on an initial descriptive investigation of a specific population of learners, measured the effects of strategy instruction on both the listening performance and self-efficacy of 68 lower-intermediate learners of French in England, against a comparison group. Moreover, the effects of high- and low-scaffolded interventions were compared. Results suggest that the program improved listening proficiency and learners' confidence about listening. Implications for pedagogy and strategy theory are discussed.